Play in an amazonian riverine community - Reis, Daniela Castro (2012)
The research aimed to describe children’s play in an Amazonian community, relating them to the riverine context and style of life. The instruments used were the sociodemographic inventory and spontaneous play, the naturalistic observation and the field notes. Twenty-two families participated in this study, including 125 residents: 66 children / adolescents and 59 adults. Initially the community was characterized and physical space used for play was identified, associated to the social context. It was found that the play expressed a typically riverine culture, influenced by the river and the forest, representing domestic issues and aspects relating to the means of subsistence. Despite the barrier imposed by the forest and river, which limit contact between peers and prioritize the interactions within the family, the children's culture has been active, creating strategies for social gatherings, as in the case of the school and the soccer field. It is concluded that the riverine culture linked to the typically Amazonian contexts, provide different and specific ways to play. Keywords: Amazon region, Children’s play, community, child, adolescent.